2013
DOI: 10.3389/fpsyg.2013.00430
|View full text |Cite
|
Sign up to set email alerts
|

How few and far between? Examining the effects of probe rate on self-reported mind wandering

Abstract: We examined whether the temporal rate at which thought probes are presented affects the likelihood that people will report periods of mind wandering. To evaluate this possibility, we had participants complete a sustained-attention task (the Metronome Response Task; MRT) during which we intermittently presented thought probes. Critically, we varied the average time between probes (i.e., probe rate) across participants, allowing us to examine the relation between probe rate and mind-wandering rate. We observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
123
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(152 citation statements)
references
References 11 publications
(28 reference statements)
13
123
3
Order By: Relevance
“…When examining Medium-and High-Confidence reports, we observed marginal differences in Variability across periods of on-task and mind-wandering periods, t{21) = 1.76, SE = 0.22, p = .094, d = 0.38, and f(21) = 1.95, SE = 0.23, p = .065, d = 0.42, respectively. It is important that in both the Medium-and the High-Confidence conditions, the effects were consistent with previous work (e.g., Seli et al, 2014;Seli, Cheyne, & Sniilek, 2013;Seli, Carriere, et al, 2013), and when employing 1-tailed t tests, both effects were significant (ps = .047. and .033, respectively).…”
Section: Variance As a Function Of Probe Report And Confidence Ratingsupporting
confidence: 85%
See 1 more Smart Citation
“…When examining Medium-and High-Confidence reports, we observed marginal differences in Variability across periods of on-task and mind-wandering periods, t{21) = 1.76, SE = 0.22, p = .094, d = 0.38, and f(21) = 1.95, SE = 0.23, p = .065, d = 0.42, respectively. It is important that in both the Medium-and the High-Confidence conditions, the effects were consistent with previous work (e.g., Seli et al, 2014;Seli, Cheyne, & Sniilek, 2013;Seli, Carriere, et al, 2013), and when employing 1-tailed t tests, both effects were significant (ps = .047. and .033, respectively).…”
Section: Variance As a Function Of Probe Report And Confidence Ratingsupporting
confidence: 85%
“…Thus far, we have reported results that indicate relations between mind-wandering propensity and per formance for individuals with high confidence but not for individuals with low confidence. Also of interest was whether, at the withinsubjects level, performance differences between self-reported periods of on-task focus and mind wandering would vary as a function of low, medium, or high confidence.1 In particular, and on the basis of previous research (e.g., Seli et al, 2014;Seli, Carriere, et al, 2013), we expected to observe more response variability during self-reported periods of mind wandering relative to on-task periods, and hypothesized that this difference would be greater for High-relative to Low-Confidence reports be cause High-Confidence reports should more accurately reflect partic ipants' true mental state. In addition, we expected that results corre sponding to Medium-Confidence reports would be intermediate between those corresponding to the Low-and High-Confidence re ports.…”
Section: Between-subjects Analysesmentioning
confidence: 99%
“…Carrier, Levene, & Smilek, 2013). Zedelius, Broadway, and Schooler (2015) also showed that participants were able to improve the accuracy of their thought-state reports when incentivized to do so.…”
Section: Mind-wandering Probe Framing 12mentioning
confidence: 96%
“…The act of reporting itself could potentially reengage the participant, leading to underestimated rates of mind wandering. Furthermore, if a probe-caught method is used, there is a limit to the number of times that participants can be probed, because probing both can be disruptive and can too frequently lead to lower reported mind-wandering rates (Seli, Carriere, Levene, & Smilek, 2013). On the flip side, infrequent probing could lead to underestimated mind-wandering rates.…”
Section: Abstract Mind Wandering Reading Eye Gaze Machine Learningmentioning
confidence: 99%